The Effect of Kinesio Taping in the Ankle Sprains of Athletes - Mehdi Ghorbani; Bijan Goodarzi (Annals of Applied Sport Science, 2017)
Objectives. The purpose of this study was the importance of applying Kinesio tape (KT) in relieving the pain in athletes' ankles using Y balance test and star.